Association of SPP1 and NCAPG genes with milk production traits in Chinese Holstein cows: polymorphism and functional validation analysis - Chuanchuan Wang; Chuanchuan Wang; Yafei Chen; Jinyan Zhao; Jinyan Zhao; Xiaofang Feng; Xiaofang Feng; Ruoshuang Ma; Ruoshuang Ma; Hua Wang; Hua Wang; Lin Xue; et al. (Frontiers in Veterinary Science)
Milk production traits play an important role in dairy cattle breeding, and single nucleotide polymorphisms can be used as effective molecular markers for milk production trait marker-assisted breeding in dairy cattle. Based on the results of the preliminary GWAS, candidate genes SPP1 and NCAPG associated with milk production traits were screened. In this study, the aim was to screen and characterize the SNPs of SPP1 and NCAPG genes about milk production traits. Two SNPs and one haplotype block of the SPP1 gene and four SNPs and one haplotype block of the NCAPG gene were obtained by amplification, sequencing and association analysis, and all six SNPs were located in the exon region. Association analysis showed that all six SNPs were significantly associated with milk protein percentage. Linkage disequilibrium analysis showed that 2 SNPs of SPP1 (g. 36,700,265 C > T and g. 36,693,596 C > A) constituted a haplotype that correlated with milk protein percentage, and the dominant haplotype was H2H2, which was CCTT. 4 SNPs of NCAPG (g. 37,342,705 C > A, g. 37,343,379 G > T, g. 37,374,314 C > A and g. 37,377,857 G > A) constituted a haplotype associated with milk protein percentage, 305-days milk protein yield and 305 days milk yield. Tissue expression profiling results revealed that SPP1 and NCAPG had the highest expression in mammary tissue. Interference with SPP1 and NCAPG inhibited the proliferation of Bovine mammary epithelial cells. (BMECs), down-regulated the expression of PCNA, CDK2 and CCND1, up-regulated the expression of BAX and BAD, and promoted apoptosis. Reduced triglyceride synthesis in BMECs, down-regulated the expression of DGAT1, DGAT2, LPIN1, and AGPAT6.SPP1 and NCAPG are involved in the synthesis of milk proteins, and interfering with SPP1 and NCAPG decreased the secretion of β-casein, κ-casein, and αs1-casein, as well as up-regulated the CSN2 and CSN3 expression. The above results indicate that the SNP loci of SPP1 and NCAPG can be used as potential molecular markers to improve milk production traits in dairy cows, laying the foundation for marker-assisted selection. It also proves that SPP1 and NCAPG can be used as candidate key genes for milk production traits in dairy cows, providing new insights into the physiological mechanisms of lactation regulation in dairy cows.